Redesigning Literacy: Our Story - Johannah D Baugher; Victoria Seeger (Educational Considerations, 2022)
This manuscript details efforts to redesign a graduate literacy program guided by two, full-time faculty members to better meet candidates’ needs in an online learning environment supported with relevant and current curricula. Through professional literature, intentional curriculum, and authentic field experiences, program coursework is closely linked, easily allowing candidates to see and experience relationships across course content, better aligning with K-12 instructional practices. As a result of candidates’ completion of this program, they are steeped in best literacy practices and interventions, which equip them to celebrate their autonomy in philosophical beliefs as it relates to their identity as a literacy professional and leader.
Keywords: literacy curriculum; graduate reading programme; redesign programmes; literacy professional; online learning; action research